2019
DOI: 10.1177/1747021819850382
|View full text |Cite
|
Sign up to set email alerts
|

The role of orthography in second-language spoken word production: Evidence from Tibetan Chinese bilinguals

Abstract: Evidence suggests that spoken language production involves involuntary access to orthographic representations, both in languages with alphabetic and non-alphabetic scripts. An unexplored question is whether the role of orthography varies as a function of the language being native or non-native to the individual. Native (L1) and non-native (L2) languages differ in important aspects, that is, lexical representations in L2 might be less well established, but acquired at least partly via reading, and these unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Next, due to the task design, we were unable to account for why participants of greater Num_Chinese experienced greater lexical competition. For instance it is possible that participants consciously or unconsciously used knowledge of radicals during search 63,64 . Given the constraints of the task, and the low phonological consistency of radicals, this search criteria would likely lead to spurious neighbors and thus the effect of producing neither high successive neighbors nor immediate neighbors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, due to the task design, we were unable to account for why participants of greater Num_Chinese experienced greater lexical competition. For instance it is possible that participants consciously or unconsciously used knowledge of radicals during search 63,64 . Given the constraints of the task, and the low phonological consistency of radicals, this search criteria would likely lead to spurious neighbors and thus the effect of producing neither high successive neighbors nor immediate neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…Naming latencies of colored line drawings were facilitated for words that shared radicals (components of Chinese characters) 64 despite characters never being exposed to the participants during the task. Using the same paradigm, Tibetan L2 speakers of Mandarin showed that interactivity of Chinese orthography and phonological information during speech production occurs for L2 speakers as well 63 .…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to acquiring an additional language later in life, it has been well documented that many learning hurdles arise from the fine-grained similarities and dissimilarities between different sound systems in contact that impinge on the perception of non-native sounds, leading to miscategorization and difficulties in production (ESCUDERO, 2011;SMILJANIC, 2011). More recently, orthography also started to be modeled as part of the knowledge that underlies L2 speech acquisition and processing (BASSETTI; ATKINSON, 2015;ESCUDERO, 2011;DAMIAN, 2019b;JÄRVIKIVI, 2013;VEIVO et al, 2018).…”
Section: Preliminary Remarksmentioning
confidence: 99%